Structural, Elastic, Electronic, Magnetic, and Half-Metallic Properties of Full-Heusler Compounds Fe2LiZ (Z = Ge and Si): A First-Principles Study - Yufeng Wen; Yanlin Yu; Zhangli Lai; Xianshi Zeng (Metals)
The structural, elastic, electronic, magnetic, and half-metallic properties of full-Heusler <semantics>Fe2</semantics>LiSi and <semantics>Fe2</semantics>LiGe compounds were investigated using first-principles calculations. Among the studied configurations, the cubic XA structures in the ferromagnetic state for both compounds are the most stable. They exhibit mechanical stability, elastic anisotropy, and ductility. Compared to <semantics>Fe2</semantics>LiGe, <semantics>Fe2</semantics>LiSi demonstrates higher stability, stronger anisotropy, greater brittleness, higher Debye and melting temperatures, and a smaller Grüneisen parameter. Both compounds exhibit metallic majority-spin channels and semiconducting minority-spin channels. At the equilibrium lattice constant, <semantics>Fe2</semantics>LiSi and <semantics>Fe2</semantics>LiGe exhibit half-metallic gaps of 0.141 eV and 0.179 eV, respectively. Both compounds exhibit 100% spin-polarization ratio in specific lattice constant ranges. The total magnetic moment per formula unit (3.000 <semantics>μB</semantics>) follows the generalized Slater–Pauling rule and depends on Fe atomic magnetic moments. These properties indicate that <semantics>Fe2</semantics>LiSi and <semantics>Fe2</semantics>LiGe hold promise for spintronic applications.